2017
DOI: 10.1186/s13561-017-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

Health expenditure and economic growth - a review of the literature and an analysis between the economic community for central African states (CEMAC) and selected African countries

Abstract: African leaders accepted in the year 2001 through the Abuja Declaration to allocate 15% of their government expenditure on health but by 2013 only five (5) African countries achieved this target. In this paper, a comparative analysis on the impact of health expenditure between countries in the CEMAC sub-region and five other African countries that achieved the Abuja declaration is provided. Data for this study was extracted from the World Development Indicators (2016) database, panel ordinary least square (OLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
188
3
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(218 citation statements)
references
References 35 publications
21
188
3
6
Order By: Relevance
“…(2016) exposed a health-growth causal correlation for a panel of 51 states over 1995, and Piabuo and Tieguhong (2017 also found the same nexus for CEMAC (the Central African Economic and Monetary Community) countries.…”
Section: Literature Reviewmentioning
confidence: 78%
“…(2016) exposed a health-growth causal correlation for a panel of 51 states over 1995, and Piabuo and Tieguhong (2017 also found the same nexus for CEMAC (the Central African Economic and Monetary Community) countries.…”
Section: Literature Reviewmentioning
confidence: 78%
“…Health is increasingly being recognized across the world as a key aspect of development and economic wellbeing of individuals and nations (Piabuo and Tieguhong, 2017). Indeed, there is widespread consensus in academic and policy circles that apart from being a human right, health leads to significant economic gains (Bloom et al, 2001;and Well, 2007).…”
Section: Introducationmentioning
confidence: 99%
“…Furthermore, existing studies on African have not sufficiently tackled country-specific characteristics. Some cross-country studies that exist such as Kouassi et al (2018) and Piabuo and Tieguhong (2017) are specific to some subregions of Africa. This paper empirically examines the relationship between healthcare and economic growth in Africa using a panel data regression framework.…”
Section: Introducationmentioning
confidence: 99%
“…Investigating the determinants of health expenditure is a critical issue in health economics research and literature (1). In spite of the positive effects of spending on healthcare, such as its impacts on economic growth through investment in health (2), less developed and developing countries have no enough financial resources for health sectors due to the low-income level. This leads governments to transfer financial resources from other sectors to the health sector and that is why the production level may decrease, especially in less developed and developing countries (3).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated different factors affect-ing health expenditures both in micro and macro levels, and showed that income is a very important factor that explains the level and growth of health expenditures among different nations (1). Prior research, predominantly in Organization for Economic Co-operation and Development (OECD) countries, reported that income elasticity was significantly above unity (1,2,4). In developing nations, most studies show that this elasticity was below the unity and therefore, concluded that health is a necessary good (1,3).…”
Section: Introductionmentioning
confidence: 99%